2007
DOI: 10.2193/2006-288
|View full text |Cite
|
Sign up to set email alerts
|

Winter Habitat Selection by Canada Lynx in Maine: Prey Abundance or Accessibility?

Abstract: We related winter habitat selection by Canada lynx (Lynx canadensis), relative abundance of snowshoe hares (Lepus americanus), and understory stem densities to evaluate whether lynx select stands with the greatest snowshoe hare densities or the greatest prey accessibility. Lynx (3 F, 3 M) selected tall (4.4‐7.3 m) regenerating clear‐cuts (11‐26 yr postharvest) and established partially harvested stands (11‐21 yr postharvest) and selected against short (3.4‐4.3 m) regenerating clear‐cuts, recent partially harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(105 citation statements)
references
References 22 publications
(38 reference statements)
8
94
0
Order By: Relevance
“…McPhee et al [9] showed that prey density was less predictive of predator efficiency than other spatial factors, suggesting that the effect of prey density may manifest more in predator searching behaviour than efficiency. In other systems, predator searching behaviour has been linked to prey density [35], prey vulnerability [36,37] and an interaction of both [38]. Thus, prey vulnerability and prey density are likely to mediate one or both of the relationships between spatial heterogeneity and components of predation found here.…”
Section: Discussionmentioning
confidence: 66%
“…McPhee et al [9] showed that prey density was less predictive of predator efficiency than other spatial factors, suggesting that the effect of prey density may manifest more in predator searching behaviour than efficiency. In other systems, predator searching behaviour has been linked to prey density [35], prey vulnerability [36,37] and an interaction of both [38]. Thus, prey vulnerability and prey density are likely to mediate one or both of the relationships between spatial heterogeneity and components of predation found here.…”
Section: Discussionmentioning
confidence: 66%
“…(2) Complexity of habitat structure was included as complex vegetation structure provides suitable microhabitat conditions for prey, representing better foraging conditions for mesocarnivores (e.g., Fuller et al, 2007;Lantschner et al, 2011), particularly in forest plantations (Moreira-Arce et al, 2015b). Complexity of habitat structure was expressed as a structural diversity index (SDI) that incorporated vertical and horizontal variation in vegetation (van Ewijk et al, 2011):…”
Section: Modeling Habitat Use With Lidar Covariatesmentioning
confidence: 99%
“…This species is an important prey species for many forest carnivores, including Canada lynx (Lynx canadensis), which is listed as threatened in the contiguous US under the Endangered Species Act (USFWS, 2000). Previous studies have used counts of fecal pellets to examine long-term population dynamics at individual sites (Malloy, 2000;Krebs et al, 2001), use of riparian set-asides in harvested areas (Darveau et al, 1998), relative abundance in different stand types in landscapes affected by various types of harvest (Newbury and Simon, 2005;Potvin et al, 2005;Fuller et al, 2007), and the impacts of precommercial thinning on population size (Sullivan et al, 2002;Ausband and Baty, 2005;Griffin and Mills, 2007;Homyack et al, 2007). Increasingly, forest managers in federal and state agencies are also using pellet counts as a way to determine which forest stands support enough hares to be considered as lynx foraging habitat, as that designation triggers particular management strategies.…”
Section: Introductionmentioning
confidence: 99%